UJI BERBAGAI MEDIA PADA AKLIMATISASI HIBRIDA DENDROBIUM - Astutik Astutik (Universitas Tribhuwana Tunggadewi, 2006)
An effort on improving value of orchid export trade offs either qualitatively or quantitatively needs sufficient orchid culture, beginning from acclimatization. The purpose of the study was to find out responses on various culture media toward the success of acclimatization of Dendrobium Hybrid resulted in appropriate media. This research used a randomly completely block design consisting of three treatments, i.e. broken bricks + edible fern, broken bricks + fresh coconut fibre, and broken bricks + coconut fibre compost. Every treatment was replicated nine times. The observed parameters included the beginning of new sprout of leaf, the amount of increasing leaves, the length of leaves and the width of leaves. The results showed that the treatment toward various media cultures affected all the parameters observed. A medium of broken bricks + fresh coconut fibre was the most appropriate media to acclimate orchid Dendrobium hybrid. The readily growth of bud was around 27,5 days, the highest development of leaves was around 1,81 days, the longest growth of leaves was approximately 5,08 cm and the widest growth of leaves was about 0,94 cm after 10 weeks acclimatization